Downstream effects of hippocampal sharp wave ripple oscillations on medial entorhinal cortex layer V neurons in vitro. Issue 12 (18th August 2016) - Roth, Fabian C.; Beyer, Katinka M.; Both, Martin; Draguhn, Andreas; Egorov, Alexei V.
Abstract : The entorhinal cortex (EC) is a critical component of the medial temporal lobe (MTL) memory system. Local networks within the MTL express a variety of state‐dependent network oscillations that are believed to organize neuronal activity during memory formation. The peculiar pattern of sharp wave‐ripple complexes (SPW‐R) entrains neurons by a very fast oscillation at ∼200 Hz in the hippocampal areas CA3 and CA1 and then propagates through the "output loop" into the EC. The precise mechanisms of SPW‐R propagation and the resulting cellular input patterns in the mEC are, however, largely unknown. We therefore investigated the activity of layer V (LV) principal neurons of the medial EC (mEC) during SPW‐R oscillations in horizontal mouse brain slices. Intracellular recordings in the mEC were combined with extracellular monitoring of propagating network activity. SPW‐R in CA1 were regularly followed by negative field potential deflections in the mEC. Propagation of SPW‐R activity from CA1 to the mEC was mostly monosynaptic and excitatory, such that synaptic input to mEC LV neurons directly reflected unit activity in CA1. Comparison with propagating network activity from CA3 to CA1 revealed a similar role of excitatory long‐range connections for both regions. However, SPW‐R‐induced activity in CA1 involved strong recruitment of rhythmic synaptic inhibition and corresponding fast field oscillations, in contrast to the mEC. These differences between features of propagating SPW‐R emphasize the differential processing of network activity by each local network of the hippocampal output loop. © 2016 Wiley Periodicals, Inc.